1994
DOI: 10.1063/1.357047
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed anodic oxides for III-V semiconductor device fabrication

Abstract: Articles you may be interested inAtomic layer deposited beryllium oxide: Effective passivation layer for III-V metal/oxide/semiconductor devices J. Appl. Phys. 109, 064101 (2011); 10.1063/1.3553872Pulse response of thin III/V semiconductor photocathodes A simple procedure for the rapid formation of uniform native oxides on various III-V semiconductor materials is described. A puIsed applied potential drives an anodic oxide formation process on the semiconductor immersed in a glycol:water:acid solution. Uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…18 Additionally, we found that this anodic oxide layer was able to promote the intermixing of QWL after rapid thermal annealing ͑RTA͒.…”
Section: Introductionmentioning
confidence: 92%
“…18 Additionally, we found that this anodic oxide layer was able to promote the intermixing of QWL after rapid thermal annealing ͑RTA͒.…”
Section: Introductionmentioning
confidence: 92%
“…9 The pulsed anodization technique has recently attracted attention as a new way of creating current blocking layers for ridge-waveguide quantum well laser fabrication, since it was simple, reliable, and cost-effective. 10 Pulsed anodized InGaAs single quantum well lasers grown by metalorganic chemical vapor deposition ͑MOCVD͒ were fabricated and found to have a threshold current of 5 mA. 11 The samples for this study were grown by low pressure MOCVD on the same p ϩ -GaAs wafer and thus have the same structure.…”
mentioning
confidence: 99%
“…These films are degenerately ntype (~ 10 20 cm -3 ) due to residual defects or impurities. Ti metal contacts were patterned by liftoff on the periphery of the samples, and etching performed in a standard electrochemical cell consisting of a teflon sample holder and a Pt wire cathode [2][3][4][5][6][9][10][11][12][13][14]. An unfiltered 450W Hg arc lamp ~ 15cm from the sample provided illumination of the samples, which were immersed in unstirred KOH, NaOH or H 2 O/AZ400K solutions.…”
Section: Methodsmentioning
confidence: 99%
“…It has long been recognized that the dissolution rate of semiconductor materials may be enhanced in acid or base solutions by illumination with above bandgap light [10][11][12][13][14]. The basic mechanism for their photo-enhanced etching is oxidative dissociation of the semiconductor into its component elements (thereby consuming the photogenerated holes) and the subsequent reduction of the oxidizing agent in the solution by reaction with the photogenerated electrons.…”
Section: Introductionmentioning
confidence: 99%